Pemberdayaan Masyarakat Melalui Wisatawan Perkebunan Strawberry Di Desa Segamit Kecamatan Semende Darat Ulu - Yusanti, Tiyara; Suryati, Suryati; Muslimin, Muslimin (CV. ITTC INDONESIA, 2023)
Thesis entitled Community Empowerment Through Strawberry Farming Tourists in Segamit Village, Semende Darat Ulu District. The purpose of this study 1) One of the efforts to develop and introduce existing tourist attractions and improve the quality of society starts from community development through strawberry plantation tourists. With the existence of cultural and natural attractions which are indeed tourism potential, this can be a strength for the region or the local community to start empowering their tourism potential. 2) Knowing the supporting and inhibiting factors for community development through strawberry plantation tourists in Segamit Village, Semende Darat District ulu. 1) Eddy Papilaya's theory cited by Zubaedi, that empowerment is an effort to build community capabilities, by encouraging, motivating, raising awareness of the potential possessed and trying to develop that potential into concrete actions. 2) supporting factors Where is the strategic location and beautiful natural scenery is perfect for tourism. factors inhibiting damaged road access.